EXAMINING FACTORS INFLUENCING ARCHITECTURAL INTERVENTIONS ON SHOPHOUSE FAÇADE IN KOTA BHARU, KELANTAN - Yasmin Mohd Faudzi (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This article concerns the emergence of architectural interventions on heritage shophouse facades in the study zone of Kota Bharu, Kelantan. The intense urban development in Malaysia brought on by the needs and demands from society has had a significant impact on heritage shophouses. The objective of this paper is to classify factors that influenced the architecture interventions on shophouse facades in the study area. The emergence of architectural interventions on shophouse facades was influenced by the modernisation of the urban area as well as a lack of awareness from the shophouse owners. Moreover, the lack of legislation and poor enforcement of existing legislation by the local authority has triggered the demolition of shophouse facades. A face to face interview and observation method was applied to obtain the data. Several interview session with shophouses owners and the local authority was done to answer research objectives. Observations were carried out on four selected units of shophouse facades along Jalan Temenggung in the study area. The findings exposed that besides natural causes, architectural interventions were caused by poor awareness by the building owners and the local authority; urban growth; and financial constraints. The finding may be useful to many stakeholders such as the shophouse owners themselves, local authority as well as the heritage practitioner in order to sustain and conserve the heritage shophouse as part of the national treasure.